(untitled) (Research, Society and Development, 2025)
The objective of this review was to analyze and discuss the scientific evidence regarding the relationship between periodontal disease and Type 2 Diabetes Mellitus, as well as the clinical and pathological implications for both diseases. Periodontal disease and diabetes mellitus are chronic diseases prevalent worldwide and share a complex pathogenic relationship. It is known from various scientific investigations that there is a higher risk of developing periodontitis in patients suffering from diabetes, and on the other hand, periodontal disease can have negative effects on blood sugar control and the course of systemic complications in diabetes. The investigations were limited to the period from 2018 to 2025, and the search within these databases utilized the Health Sciences Descriptors (DeCS): Periodontal Diseases; Diabetes Mellitus; Aggravation of Symptoms; comorbidity and studies that addressed the guiding question and related to the proposed objective. Systematic reviews, comparative studies, periodontal dental interventions, and their positive effects on the control of Type 2 diabetes mellitus were included. The results of this study seem to indicate that appropriate periodontal care can improve glycemic control and that, conversely, controlled Type 2 diabetes can enhance oral health.